2023
DOI: 10.3390/foods12061123
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Growth of Six Listeria monocytogenes Strains in Smoked Salmon Pâté

Abstract: In this study, the growth of six L. monocytogenes strains isolated from different fish products was quantified and modeled in smoked salmon pâté at a temperature ranging from 2 to 20 °C. The experimental data obtained for each strain was fitted to the primary growth model of Baranyi and Roberts to estimate the following kinetic parameters: lag phase (λ), maximum specific growth rate (μmax), and maximum cell density (Nmax). Then, the effect of storage temperature on the obtained μmax values was modeled by the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The maximum specific growth rate (µ max ), which is one of the most important growth kinetic parameters, can be modelled with respect to environmental factors such as temperature, NaCl concentration, water activity, and pH. Among these factors, temperature plays a key role in affecting microbial growth behaviour in food [5]. Temperature variables ranged from 2 to 11 • C for beef, 0 to 25 • C for culture medium, 0.1 to 10.4 • C for pork, and 1 to 7 • C for poultry, which means 5618 collected growth data points were in the range of 0 to 25 • C which are real temperatures to which food products are subject to in storage, delivery, and retail marketing processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum specific growth rate (µ max ), which is one of the most important growth kinetic parameters, can be modelled with respect to environmental factors such as temperature, NaCl concentration, water activity, and pH. Among these factors, temperature plays a key role in affecting microbial growth behaviour in food [5]. Temperature variables ranged from 2 to 11 • C for beef, 0 to 25 • C for culture medium, 0.1 to 10.4 • C for pork, and 1 to 7 • C for poultry, which means 5618 collected growth data points were in the range of 0 to 25 • C which are real temperatures to which food products are subject to in storage, delivery, and retail marketing processes.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalent and traditional modelling technique in predictive microbiology is the two-step modelling approach, which involves fitting the primary and secondary models sequentially. Initially, the primary model is fitted to growth data points, and then the resulting growth kinetic parameters are integrated into the secondary model, considering environmental factors such as temperature [5]. Nevertheless, the two-step modelling approach has its limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic information on specific growth rates, lag phases, biomass yields, and substrate consumption rates under different environmental conditions helps construct mathematical models that optimize and predict bioprocess outcomes [ 5 ]. In the food industry, selection of appropriate models depends on the characteristics of the microorganism and the food matrix, and their accuracy should be validated with experimental data [ 6 , 7 ]. Comparative analysis of different mathematical models has shown that specific models are suitable for different types of microorganisms and food matrices [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Posada-Izquierdo et al [ 5 ] modeled the effect of salt concentration on autochthonous isolated L. monocytogenes strains in an artisanal fresh cheese. Finally, Bolívar et al [ 6 ] quantified and modeled the growth dynamics of six L. monocytogenes strains isolated from different fish products in salmon pâté. Both studies have demonstrated the growth potential of the pathogen under all tested conditions, providing interesting data about its kinetic behavior in RTE food products with significant consumption and commercial value.…”
mentioning
confidence: 99%